Feeding the planet between food security and food safety (Glocalism: Journal of Culture, Politics and Innovation, 2014)
The issue of food is indeed a systemic problem involving fundamental aspects of the social, cultural and economic organisation of our planet. This paper focuses on the main aspects related to the concepts of food security and food safety. While the first problem mainly affects less developed countries, the second concerns diet in the developed world. They are influenced by important factors such as the structure of food distribution, the effective access to food resources, the lack of confidence about the safety of the products, and the different consumption behaviours affected by social, economic and religious factors.
Keywords: food security; food safety; food distribution; consumption behaviours; food resources